Green Synthesis of Nickel Oxide Nanoparticles and its Application in the Degradation of Methyl Red (Lafia Journal of Scientific and Industrial Research, 2024)
Environmental pollution is a threat to human health, with methyl red dye used in printing and textile dyeing being a notable pollutant that can cause eye, skin, and digestive system irritation. This study investigates the degradation of methyl red dye using nanoparticles of Nickel Oxide (NiO NPs) as photocatalysts. NiO NPs were synthesised at room temperature through thermal decomposition using antioxidant-rich extracts from strawberries (Fragaria ananassa), grapes (Vitis vinifera), and grapefruits (Citrus paradisi). Characterisation of the NiO NPs was performed using FTIR, UV-Vis spectroscopy and SEM. FTIR spectra confirmed the formation of NiO NPs with peaks between 577 – 585 cm–1. UV-Vis spectroscopy showed absorption wavelengths between 322-326 nm for the synthesised NiO NPs and a blue shift to 422-470 nm during methyl red degradation. This study presents a sustainable method for  synthesising NiO nanoparticles and demonstrates their effectiveness in environmental remediation, specifically for the removal of  pollutant dyes.